SAT0509 BODY MASS INDEX AND DISEASE ACTIVITY IN PORTUGUESE AND BRAZILIAN JUVENILE IDIOPATHIC ARTHRITIS PATIENTS: RESULTS FROM RHEUMATIC DISEASES PORTUGUESE REGISTER – REUMA.PT. (June 2019) - Neto, Agna; Mourão, Ana Filipa; Oliveira-Ramos, Filipa; Gomes, José Melo; Santos, Maria Jose; Campanilho-Marques, Raquel; Piotto, Daniela; Silva, Clovis Artur; Estanqueiro, Paula; Fonseca, Joao Eurico; Tererri, Maria T.; Canhão, Helena
Abstract : Background: The influence of body mass index (BMI) on Juvenile Idiopathic Arthritis (JIA) disease activity is poorly understood. In adults with Rheumatoid Arthritis, obesity has been associated with higher disease activity, while in JIA patients, a previous study has failed to find any association. Objectives: To investigate the relationship between BMI and JIA disease activity. Methods: This is an international, multicenter, observational, cross-sectional study. JIA patients (according to ILAR criteria) aged ≤ 18 years, registered at Reuma.pt in Portugal and Brazil were included. Data was analysed upon records from the first registered visit. Age- and sex-specific BMI percentiles (P) were calculated based on WHO growth standard charts and categorized into underweight (P<3), normal weight (3≤P≤85), overweight (8597). Disease activity was assessed by Juvenile Arthritis Disease Activity Score (JADAS-27). Univariate linear regression was used to examine the association of JADAS-27 with BMI categories. Two multivariate regression models were performed a) adjusting for age, gender, race, country, disease duration and JIA category (model 1); b) adjusting for those covariates plus use of DMARDs (model 2). Results: 255 patients included, mean age 10.1±4.7 years, mean disease duration 6.3±4.9 years; 62% female; 85% Caucasian. Thirty-two percent were persistent oligoarticular, 9% extended oligoarticular, 34% polyarticular RF+, 6% systemic, 13% enthesitis-related arthritis, 5% psoriatic arthritis and 1% undifferentiated arthritis. The prevalence of underweight, normal weight, overweight and obesity was 7.5%, 65.9%, 15.7% and 11%, respectively. In the univariate linear regression, underweight was significantly associated with higher JADAS-27, compared to normal weight (B=-9.563, p <0.001), overweight (B=-10.661, p <0.001) and obesity (B=-7.422, p =0.004). Lower age (B=-0.299, p=0.012), shorter disease duration (B=-0.396, p=0.001), black race (B=6.852, p=0.033), RF+ polyarthritis (B=7.101, p<0.001), living in Brazil (B=5.357, p=0.002) and the absence of DMARD therapy (B=4.831, p<0.001) were also associated with higher JADAS-27. In the model 1 of multivariate analysis, the same variables, except the country, remained significantly associated with higher disease activity. When DMARD therapy was added to the model (model 2), RF+ polyarthritis (B=4.447, p =0.001) and living in Brazil (B=4.728, p =0.013) were associated with higher JADAS-27. Patients with normal weight (B=-9.964, p <0.001), overweight (B=-10.316, p <0.001) and obesity (B=-9.502, p =0.001) had significantly lower activity disease, compared to underweight patients, as well as those under DMARD therapy (B=-4.858, p <0.001). Conclusion: Despite the lack of adjustment for corticosteroids use, there seems to be an independent association between underweight and higher disease activity in JIA patients. Importantly, these results suggest that active disease can impair child's weight gain. Further studies are needed to confirm these findings and understand the underlying mechanisms of this association. Disclosure of Interests: None declared